Estimación del indicador de calidad de vida para el Municipio de Envigado (2010)
ABSTRACT: This paper presents the estimation of the Indicator of Quality of Life (ICV) for the homes of the municipality of Envigado. The used statistical methodology is based on the use of the methods of Quantification of Qualitative Variables and the Analysis Nonlinear of Main Components. A description of this methodology is in Young (1981), Gifi (1990) and one brief introduction is in the Appendix. Based on the information provided by the Survey of Quality of Vida (ECV) realised year 2005 indicators were constructed to as much measure the quality of life of the homes in the urban area as rural, for the municipalities of Barbosa, Beautiful, Calda, Copacabana, Girardota, Itagüí, the Star, Sabaneta and Medellín. These indicators are a summary of different characteristics related to the house, demographic aspects of the people who compose the home, the access to the services public, and the human capital and the social security of the home. In 2007, the ECV for all the municipalities of Metropolitan Area was repeated, including the municipality of Envigado, with the aim of estimating the evolution of the indicator constructed in the 2005 in the municipalities of Barbosa, Beautiful, Calda, Copacabana, Girardota, Itagüí, the Star, Sabaneta and Medellín and measuring for the first time the conditions of life of the municipality of Envigado. In order to realise this evaluation, the Indicator of Quality of Life was used obtained in the 2005 valued with the new information of the ECV of the 2007. This document contains the update of indicator using the information of the Survey of Quality of Life of the 2009 and one description of the evolution of the ICV between years 2007 and 2009 for the municipality of Envigado.